A PD Computed Torque Control Method with Online Self-gain Tuning for a 3UPS-PS Parallel Robot. Issue 9 (20th September 2021) - Song, Xiaogang; Zhao, Yongjie; Chen, Chengwei; Zhang, Liang'an; Lu, Xinjian
SUMMARY: In this paper, an online self-gain tuning method of a PD computed torque control (CTC) is used for a 3UP S-P S parallel robot. The CTC is applied to the 3UP S-P S parallel robot based on the robot dynamic model which is established via a virtual work principle. The control system of the robot comprises a nonlinear feed-forward loop and a PD control feedback loop. To implement real-time online self-gain tuning, an adjustment method based on the genetic algorithm (GA) is proposed. Compared with the traditional CTC, the simulation results indicate that the control algorithm proposed in this study can not only enhance the anti-interference ability of the system but also improve the trajectory tracking speed and the accuracy of the 3UP S-P S parallel robot.